2017
DOI: 10.1007/s11284-017-1441-8
|View full text |Cite
|
Sign up to set email alerts
|

Edge and herbivory effects on leaf litter decomposability in a subtropical dry forest

Abstract: It is increasingly recognized that understanding the functional consequences of landscape change requires knowledge of aboveground and belowground processes and their interactions. For this reason, we provide novel information addressing insect herbivory and edge effects on litter quality and decomposition in fragmented subtropical dry forests in central Argentina. Using litter from Croton lachnostachyus (a common shrub species in the region) in a decomposition bed experiment, we evaluated whether litter quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…However, both the results herein and some previous reports suggest a positive relationship between LDMC and leaf herbivory (Lepidoptera richness in this study; Schuldt et al, 2012), probably because there are herbivores specifically adapted to tough leaves (Pérez et al, 2003) and herbivores have to consume more of less nutritious foliage to gain the same nitrogen accumulation rates (Scriber & Slansky, 1981).…”
Section: Ta B L E 2 (Continued)supporting
confidence: 50%
See 1 more Smart Citation
“…However, both the results herein and some previous reports suggest a positive relationship between LDMC and leaf herbivory (Lepidoptera richness in this study; Schuldt et al, 2012), probably because there are herbivores specifically adapted to tough leaves (Pérez et al, 2003) and herbivores have to consume more of less nutritious foliage to gain the same nitrogen accumulation rates (Scriber & Slansky, 1981).…”
Section: Ta B L E 2 (Continued)supporting
confidence: 50%
“…As mentioned above, the phyllosphere appears to be a key source for herbivore microbiomes and is moderated by tree characteristics such as leaf structure (also, LDMC is directly affected by leaf thickness, structure, and specific leaf area and reflects the ability of plants to obtain resources). LDMC and LT are usually expected to negatively associate with herbivory because structurally robust leaves are relatively difficult to consume (Pérez et al, 2003).…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
“…Studies have shown that intraspecific trait shifts in response to environmental change, including abiotic and biotic drivers (Coq et al, 2018; Henneron et al, 2017), can affect leaf decomposability. In terms of habitat fragmentation, for example, Moreno et al (2017) observed that within the same species, plants growing at the forest edge had a higher leaf carbon‐to‐nitrogen ratio and, thus, reduced litter quality, and in a common garden decomposition experiment they showed that such ITV caused a reduction in litter decomposition rates of leaves from “edge” plants. In addition, habitat fragmentation also influences litter decomposition rates by altering site conditions (Bradford et al, 2015; Wardle et al, 2004), which can themselves drive intraspecific shifts in plant traits (e.g., Moreno et al, 2017), leading to challenges in discriminating confounding “donor effects” (plant traits) from “recipient effects” (site conditions) on litter decomposition in the field.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of habitat fragmentation, for example, Moreno et al (2017) observed that within the same species, plants growing at the forest edge had a higher leaf carbon‐to‐nitrogen ratio and, thus, reduced litter quality, and in a common garden decomposition experiment they showed that such ITV caused a reduction in litter decomposition rates of leaves from “edge” plants. In addition, habitat fragmentation also influences litter decomposition rates by altering site conditions (Bradford et al, 2015; Wardle et al, 2004), which can themselves drive intraspecific shifts in plant traits (e.g., Moreno et al, 2017), leading to challenges in discriminating confounding “donor effects” (plant traits) from “recipient effects” (site conditions) on litter decomposition in the field. So far, previous studies investigating drivers of litter decomposition in fragmented forests focused on either leaf trait effects alone using common garden decomposition experimental manipulation (e.g., Moreno et al, 2017) or environmental drivers using common litter substrate experiments (e.g., Didham, 1998; Riutta et al, 2012), leaving the relative effects of these collinear drivers of litter decomposition elusive in fragmented forests.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the litter influences mineralization rates by microbial communities, which play a major role in controlling soil N cycling (Aerts et al, 2006;Wallenstein et al, 2007). The C:N is a ratio of the mass of C to N in a substance and can indicate the decomposability of the material (Di Palo & Fornara, 2015;Moreno et al, 2017). For example, graminoid and moss vegetation have a higher C:N ratio relative to other litters (e.g.…”
Section: Evidence and Mechanisms For Shrub Expansionmentioning
confidence: 99%